(untitled) (Journal Edutama Multidisciplinary Indonesian, 2024)
This study aims to analyze the influence of work environment and work discipline on employee performance in the warehouse division at PT. Balina Agung Perkasa Bekasi Branch. The research method uses a quantitative approach with a saturated sampling technique involving all 40 warehouse division employees as respondents. Data collection was conducted through questionnaires and analyzed using multiple linear regression. The results show that the work environment has a positive and significant effect on employee performance (t count 6.099 > t table 2.026; sig. 0.000 < 0.05). However, work discipline does not significantly affect employee performance (t count -0.108 < t table 2.026; sig. 0.914 > 0.05). Simultaneously, the work environment and work discipline significantly influence employee performance (F count 22.684 > F table 3.25; sig. 0.000 < 0.05). This study concludes that improving the quality of the work environment can enhance employee performance, while the impact of work discipline on performance needs further investigation. These findings provide important implications for the management of PT. Balina Agung Perkasa in efforts to improve employee performance in the warehouse division